Firm‐Specific Human Capital: A Skill‐Weights Approach - Lazear, Edward P. (Journal of Political Economy, 2009)
The theory of human capital is agnostic on what constitutes firm-specific skills. The theory specifies that specific skills contribute to productivity only at the current firm. A broader approach lets all skills be general, but firms use them with different weights attached. For example, computer programming, economics, and accounting are general skills, but there may be only one firm that wants workers trained in all three. One implication is that wage profiles and the split of human capital costs depend on thickness of the market. Another is that firms pay for what appears to be general training. (c) 2009 by The University of Chicago. All rights reserved.